Comparison the effectiveness of Emotion-Focused Couple and Acceptance and Commitment Therapies on Marital Forgiveness in Incompatible Couples - Hossein Zaeimi; Ali Reza Rajaei; Mohammad Reza Saffaran Tousi; Hamid Nejat (Shahid Beheshti University of Medical Sciences, 2023)
Background: Using effective interventions to reduce incompatibility among couples can play a role in preventing divorce in the family. The present study aimed to compare the effectiveness of emotion-focused couple therapy (EFCT) and acceptance and commitment therapy (ACT) on forgiveness in incompatible couples. Methods: The present research is a quasi-experimental study that was done on couples referred to a family therapy clinic in Torbat-e-Jam City. Here, 24 incompatible couples were selected through purposive methods and randomly replaced in three groups. The first and second groups (8 couples in each group) received emotion-focused couples and acceptance and commitment therapies, respectively, and the third group as control (8 couples) did not receive any intervention during the study period. All three groups were evaluated before and after the intervention with a standard questionnaire of Bagarozi forgiveness (2001). Data were analyzed through SPSS software version 20 and covariance analysis. Results: The findings revealed that both therapies of EFCT and ACT had a meaningful effect on forgiveness (P < 0.001, F = 41.73, and P = 0.031, F = 5.13; respectively); while the results indicated that the two groups under intervention have no significant difference in terms of effectiveness on the variable of forgiveness (P=0.63, F=0.23). Conclusion: According to the results and effectiveness of the two therapy groups, it is recommended to use a combination of approaches according to the therapeutic goals.